2023
DOI: 10.1186/s13072-023-00489-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifier alpha-ketoglutarate modulates aberrant gene body methylation and hydroxymethylation marks in diabetic heart

Abstract: Background Diabetic cardiomyopathy (DCM) is a leading cause of death in diabetic patients. Hyperglycemic myocardial microenvironment significantly alters chromatin architecture and the transcriptome, resulting in aberrant activation of signaling pathways in a diabetic heart. Epigenetic marks play vital roles in transcriptional reprogramming during the development of DCM. The current study is aimed to profile genome-wide DNA (hydroxy)methylation patterns in the hearts of control and streptozotoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For example, several studies have shown the induction of KDM5A and B in the context of heart failure, suggesting a pathogenic role for these proteins likely through the activation of the fetal gene program. Given the many pleiotropic roles of α-KG, it is conceivable that the rise in α-KG levels could potentially result in the activation of TET enzymes [ 8 10 ] . TET protein has been shown to play a significant role in the proliferation of cardiac myocytes and the expression of [ 9 ] cardiac genes and thereby may contribute to CM proliferation and/or other phenotypes in conjunction with, or independent of KDM5s in the Cpt1b knockout CMs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies have shown the induction of KDM5A and B in the context of heart failure, suggesting a pathogenic role for these proteins likely through the activation of the fetal gene program. Given the many pleiotropic roles of α-KG, it is conceivable that the rise in α-KG levels could potentially result in the activation of TET enzymes [ 8 10 ] . TET protein has been shown to play a significant role in the proliferation of cardiac myocytes and the expression of [ 9 ] cardiac genes and thereby may contribute to CM proliferation and/or other phenotypes in conjunction with, or independent of KDM5s in the Cpt1b knockout CMs.…”
mentioning
confidence: 99%
“…3. Recent studies have documented the role of the KDM5 family of proteins in the maturation of cardiac myocytes [7] . It was shown that the levels of KDM5 gradually decrease during the maturation of CM and are negligible in the mature adult CM.…”
mentioning
confidence: 99%